Pengaruh Kegiatan Keagamaan terhadap Perilaku Remaja dalam Membentuk Karakter dan Moral di Lingkungan Sosial - Hardiansyah Rasyidin; Syamzaimar Syamzaimar (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study aims to determine the influence of religious activities on adolescent behavior in daily life. Adolescence is a developmental phase that is vulnerable to various environmental influences, both positive and negative. Therefore, religious activities are considered one of the efforts to develop character and morality that can shape adolescents’ behavior in a positive direction. This study employed a quantitative approach using a survey method. Data were collected through observation, questionnaires, and documentation involving adolescents who actively participated in religious activities at school and within the community. The data were analyzed using simple statistical analysis techniques to identify the relationship and influence between the intensity of religious activities and adolescent behavior. The results showed that religious activities have a positive influence on adolescent behavior, particularly in aspects such as discipline, responsibility, politeness, social awareness, and self-control. Adolescents who actively participate in religious activities tend to demonstrate better behavior compared to those who are less involved. In addition, religious activities also contribute to reducing deviant behaviors among adolescents, such as juvenile delinquency, negative social interactions, and lack of respect toward parents and teachers. Therefore, religious activities can serve as an effective means of character building and strengthening moral values among adolescents in the modern era.